Jejunal Diverticulosis: Presenting As Peritonitis - Vikas Chalotra; Puneet Bansal; Natasha Nuna; Shifali Joshi; Sarbjeet Singh; Aman Bharti (Asian Journal of Medical Research, 2019)
Jejunal diverticular perforation is a rare complication of jejunal diverticular disease and few cases have been reported in the literature. Jejunal diverticula have a prevalence of approximately 1% in the general population. Pathophysiology of chronic symptoms is related to either intestinal dyskinesia or bacterial overgrowth from blind loop syndrome due to stasis in diverticular lumen. Patients may develop malabsorption, steatorrhea, and megaloblasticanaemia from vitamin B12 deficiency. Conventional enteroclysis and CT enteroclysis is beneficial for diagnosis of jejunal diverticular disease. Jejunal diverticular perforation is very rare. Clinically, the diagnosis is challenging and mimics with other causes of acute abdomen. Presentation varies widely from asymptomatic to non specific symptoms to acute abdomen with catastrophic consequences. Here, we present a rare case of jejunal diverticular perforation.